DIGITAL MARKETING AND ENTREPRENEURIAL MARKETING IN OPTIMIZING MILLENNIAL CONSUMER LOYALTY THROUGH CONSUMER SATISFACTION - Yanti Pujiastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Millennial generation loyalty to a product needs to be supported by a strategy that leads to digitalization and innovation. Evidence of the effect of digital marketing, entrepreneurial marketing on customer satisfaction is tested in this study. The effect of intervening consumer satisfaction on the relationship between digital marketing, entrepreneurial and consumer loyalty is included in the test. The population is the millennial generation who have visited Semarang and obtained 103 samples. The data analysis technique used regression and path analysis. The results of the study found a significant effect of digital marketing on consumer satisfaction (0.001) and consumer loyalty (0.000) and a significant influence of entrepreneurial marketing on consumer satisfaction (0.000). Consumer satisfaction is not proven to have an effect on consumer loyalty (0.163) so it is not proven to have an intervening effect. Digital marketing can be used to increase millennial consumer satisfaction and loyalty in the tourism sector. Future research can provide certain conditions for the sample so that the results are more optimal. Keywords: digital marketing, entrepreunerial marketing, consumer loyalty, consumer satisfaction